Suppression of Intimal Hyperplasia by a 5-lipoxygenase Inhibitor, MK-886: Studies with a Photochemical Model of Endothelial Injury - Kondo, Kazunao; Umemura, Kazuo; Ohmura, Tomohiro; Hashimoto, Hisakuni; Nakashima, Mitsuyoshi (Thrombosis and Haemostasis, 1998)
Intimal thickening is a major complication following percutaneous transluminal coronary angioplasty, which leads to restenosis and requires reoperation. We have investigated the effect of a 5-lipoxygenase inhibitor, MK-886, a leukotriene B4 (LTB4) receptor antagonist, ONO-4057 or a LTC4 and LTD4 receptor antagonist, ONO-1078, on intimal thickening. Photochemical reaction between green light and systemically administered Rose Bengal produced intimal thickening in the rat femoral artery. Each drug was administered orally, once a day for 7 days, starting just after the endothelial injury. Both MK-886 administration, 10 mg/kg, and ONO-4057 administration, 100 mg/kg, suppressed intimal thickening level examined three weeks after endothelial injury, while similarly administered ONO-1078 did not. In cultured rat-derived smooth muscle cells, LTB4, an active metabolite of 5-lipoxygenase whose biosynthesis in air pouch exudate was suppressed by MK-886, stimulated cell migration. Based on these observations, the 5-lipoxygenase may have a key role in intimal thickening via its metabolites such as LTB4.